Caffeine and Glucose Metabolism at Rest Period, During, and Post Exercise in Diabetes Mellitus: A Systematic Review - Da Silva, Luiz Augusto; Wouk, Jessica; Reis Weber, Vinicius M.; de Almeida, Pablo; Lacerda Martins, Julio Cesar; Maneck Malfatti, Carlos Ricardo; Osiecki, Raul (Current Nutrition & Food Science, 2018)
Purpose: Diabetes Mellitus (DM) is correlated with a group of diseases related to the metabolism of glucose that is increasingly affecting the population, being considered a public health problem. Exercise increases absorption of glucose by the muscles during, pre- and post- periods of effort, therefore, it is an excellent treatment strategy to maintain the glycemic control of diabetic patients. Caffeine intake enhances Ca2+ concentration in β pancreatic cells, affecting insulin secretion. Materials and Methods: Systematic review with a sample of six scientific papers published in academic journals. Only studies involving soccer players (professionals and amateurs, except goalkeepers) were included in this review. Results and Conclusion: Studies included in this review concluded that caffeine might act in several ways in glucose metabolism; however, more researches are necessary to elucidate the real effects of this compound in the organism.
Keywords: glycemia